2000
DOI: 10.1016/s0022-5347(05)67980-3
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Diagnostic Tools to Prove Erectile Dysfunction: Consequences for Reimbursement?

Abstract: Erectile dysfunction could not be defined by pharmacostimulated erections but relevant erectile dysfunction was honestly reported. New and reliable tests for clinical assessment are required to support the application for reimbursement of treatment expenses for erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A body of compelling scientific evidence indicates that pharmacological testing and the duplex Doppler ultrasonography are neither valid nor reliable measures for determining the presence or severity of ED. 67 These tests are known to have low sensitivity, specificity, and reproducibility. 67 Therefore, it is not surprising that physiological or pharmacological tests may be at odds with validated patient reports of sexual dysfunction, including the SHIM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A body of compelling scientific evidence indicates that pharmacological testing and the duplex Doppler ultrasonography are neither valid nor reliable measures for determining the presence or severity of ED. 67 These tests are known to have low sensitivity, specificity, and reproducibility. 67 Therefore, it is not surprising that physiological or pharmacological tests may be at odds with validated patient reports of sexual dysfunction, including the SHIM.…”
Section: Discussionmentioning
confidence: 99%
“…67 These tests are known to have low sensitivity, specificity, and reproducibility. 67 Therefore, it is not surprising that physiological or pharmacological tests may be at odds with validated patient reports of sexual dysfunction, including the SHIM. 54,63 Even if such laboratory tests were accurate for a limited purpose, sexual (and even erectile) dysfunction has multiple facets that extend beyond the limited range of function measured by such laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…1 -4 There is considerable controversy about the relative importance of each of these factors in the initiation and maintenance of an erection, especially the role of serum levels of testosterone. 2,5 Several studies have documented that aging in men is associated with a decrease in sexual interest and activity, and particularly with an increased prevalence of erectile dysfunction. 1,6 In the MMAS study a prevalence of 20% of hypogonadism for the men over 55 y of age was observed, when the TT levels below the normal rate for young, healthy subjects were considered.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of blood flow parameters, intracavernous pressure or venous leakage on pharmacostimulated erections evaluate aspects of erectile function under nonsexual conditions. This may explain the inconsistent results between the patient's self-evaluation and measured parameters [13]. The concept of complete smooth muscle relaxation [14] by injecting repetitive doses of intracavernous vaso-active drugs to its maximal effect may overcome the limits of tests based on pharmacostimulation.…”
Section: Discussionmentioning
confidence: 99%